Molecular classification of nemaline myopathies: "nontyping" specimens exhibit unique patterns of gene expression - Sanoudou, D.; Frieden, L. A.; Haslett, J. N.; Kho, A. T.; Greenberg, S. A.; Kohane, I. S.; Kunkel, L. M.; Beggs, A. H. (Neurobiol DisNeurobiol DisNeurobiol Dis, 2004)
Nemaline myopathy (NM) is a slowly progressive or nonprogressive neuromuscular disorder caused by mutations in genes encoding skeletal muscle sarcomeric thin filament proteins. It is characterized by great heterogeneity at the clinical, histopathological, and genetic level. Although multiple molecular pathways are commonly affected in all NM patients, little is known about the molecular characteristics of muscles from patients in different NM subgroups. We have analyzed a group of global gene expression data sets for transcriptional patterns characteristic of particular nemaline myopathy classes. Differential expression between disease subgroups was primarily seen in mitochondrial-, structural-, and transcription-related genes. Multiple lines of evidence support the hypothesis that muscles from cases with "nontyping" NM, although clinically classified as typical NM, share a unique pathophysiological state and are characterized by distinct patterns of gene expression. Determination of the specific molecular differences in NM subgroups may eventually lead to improved prognostic determinations and treatment of these patients.
Sanoudou, DespinaFrieden, Leslie AHaslett, Judith NKho, Alvin TGreenberg, Steven AKohane, Isaac SKunkel, Louis MBeggs, Alan HengP01 NS040828/NS/NINDS NIH HHS/P01 NS40828/NS/NINDS NIH HHS/R01 AR44345/AR/NIAMS NIH HHS/Comparative StudyResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, P.H.S.2004/04/02 05:00Neurobiol Dis. 2004 Apr;15(3):590-600. doi: 10.1016/j.nbd.2003.12.013.
Keywords: Base Sequence; Fluorescent Antibody Technique; gene expression; gene expression profiling; Humans; Muscle, Skeletal/*physiology; Myopathies, Nemaline/*classification/*genetics; Oligonucleotide Array Sequence Analysis; Polymorphism, Single-Stranded Conformational; Reverse Transcriptase Polymerase Chain Reaction; Troponin T/genetics